1997
DOI: 10.1021/ie970069o
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Aqueous Pollutants Using Ultrasound:  Salt-Induced Enhancement

Abstract: Ultrasound can be used to oxidize aqueous pollutants; however, due to economic reasons, higher oxidation/destruction rates are needed. This study reports enhancements of reaction rates by the addition of sodium chloride salt. Using 20 kHz ultrasound, large salt-induced enhancements are observed6-fold for chlorobenzene, 7-fold for p-ethylphenol, and 3-fold for phenol oxidation. The reaction rate enhancements are proportional to the diethyl ether−water partitioning coefficient of the pollutants. It appears that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(64 citation statements)
references
References 12 publications
3
58
1
2
Order By: Relevance
“…Seymour et al found an increase in oxidisation reactions occurring at the bubble surface with the use of sodium chloride [210]. The group suggested that there was an increase in the ionic strength of the liquid which drove organic pollutants to the region.…”
Section: Salt Solutionsmentioning
confidence: 99%
“…Seymour et al found an increase in oxidisation reactions occurring at the bubble surface with the use of sodium chloride [210]. The group suggested that there was an increase in the ionic strength of the liquid which drove organic pollutants to the region.…”
Section: Salt Solutionsmentioning
confidence: 99%
“…It shows that the efficiency of It was found that the oxidation of organic compounds by sonocation highly depends on the concentration [29,30]. That means the expose with ultrasound covers more in low concentration.…”
Section: Resultsmentioning
confidence: 96%
“…57 Under the rise of ionic strength induced by the presence of salts, the solute is expected to migrate from bulk solution to the interface of the bubble/solution where the concentration of hydroxyl radicals is high and degradation is likely to occur fast. 58 Simultaneously, the presence of salts reduces the amount of dissolved gas, and hence the bubble coalescence will also be reduced, resulting in a greater number of small bubbles of higher sonochemical activity. 37 However, the lower positive effect of seawater compared to those of mineral and river waters was attributed to the ultrasound attenuation due to the high solution viscosity and surface tension induced by the high quantity of salts presents in seawater.…”
Section: Effect Of Environmental Matricesmentioning
confidence: 99%